2019
DOI: 10.1016/j.apmr.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

From Hospital to Home to Participation: A Position Paper on Transition Planning Poststroke

Abstract: Based on a review of the evidence, members of the American Congress of Rehabilitation Medicine Stroke Group's Movement Interventions Task Force offer these five recommendations to help improve transitions of care for patients and their caregivers: (1) improving communication processes, (2) utilizing transition specialists, (3) implementing a patient-centered discharge checklist, (4) utilizing standardized outcome measures, and (5) establishing partnerships with community wellness programs. Due to changes in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 140 publications
(119 reference statements)
0
50
0
Order By: Relevance
“…These areas of agreement and difference may tentatively indicate which aspects of the ESD model are core (and transferable as essential elements), and which are peripheral (and therefore adaptable to local conditions) [17]. Given the variability in ESD models of care being implemented globally [4,15], further research to describe its core and peripheral characteristics is important to guide its effective use.…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…These areas of agreement and difference may tentatively indicate which aspects of the ESD model are core (and transferable as essential elements), and which are peripheral (and therefore adaptable to local conditions) [17]. Given the variability in ESD models of care being implemented globally [4,15], further research to describe its core and peripheral characteristics is important to guide its effective use.…”
Section: Plos Onementioning
confidence: 98%
“…ESD models of care share common features and components, including multidisciplinary team members, a workforce with specialist stroke care knowledge and the provision of services in the community [14,15]. However, ESD is has been implemented variably around the world, particularly in regards to recommended full time staff loadings and intensive treatment duration.…”
Section: Introductionmentioning
confidence: 99%
“…Although there can be variability in ESD protocols (for example team composition, service locations and the provision of additional supports such as transport), all models share some key features and components. In addition to the consensus study already referred to, the distinguishing characteristics of ESD have also been reported in a further Delphi study from the United Kingdom (Fisher et al, 2013), and a recent position paper (Miller et al, 2019). As shown in Table 1, the ESD model utilised in this study reflected many of the key features and components identified in these consensus documents.…”
Section: Interventionmentioning
confidence: 52%
“…17 Internationally, delivering effective stroke care has changed over the years as an understanding of stroke has increased, moving from individual care to a more comprehensive health system approach. 18 The majority of people with stroke in SA may have no or limited access to stroke care and rehabilitation. 3 19 Stroke rehabilitation is limited in the first instance by insufficient rehabilitation facilities in the public sector, as well as inadequate intensity of inpatient rehabilitation, and lack of outpatient or community-based rehabilitation.…”
Section: Care For People With Strokementioning
confidence: 99%
“… 17 Internationally, delivering effective stroke care has changed over the years as an understanding of stroke has increased, moving from individual care to a more comprehensive health system approach. 18 …”
Section: Introductionmentioning
confidence: 99%